Microstructural characterization of Au-In Thin film deposited by electron beam evaporation - Norliza Ismail; Muhammad Azmi Abdul Hamid; Azman Jalar (Universiti Kebangsaan Malaysia, 2009)
The microstructure and phase formation of Au-In thin film deposited by e-beam evaporation technique has been studied. Single crystals of rocksalt were used as the substrates. The chamber pressure during deposition was about 2.5  10-5 torr and substrate temperature was 35ºC. Three types of samples were prepared namely Au, In and Au-In thin films. Microstructure and chemical composition of these thin films were characterized by transmission electron microscopy (TEM) and X-ray photoelectron spectrometer (XPS) respectively. TEM micrograph reveals island structures for both Au and In thin film on the rocksalt substrate, with the In island size distribution is about 9-30 nm compared to Au island in the range of 3-10 nm. The growth of islands instead of smooth film indicates that Au and In thin films follow the Volmer- Weber growth mode. However, island structures were not present on Au-In thin films which most probably follow the Frank van de Merwe growth mode. XPS analysis indicates intermetallic compound was not present in the Au-In thin film suggesting that diffusion process in the interface of Au and In films is minimal.